Growth of HIV-1 Molecular Transmission Clusters in New York City. (14th July 2018) - Wertheim, Joel O; Murrell, Ben; Mehta, Sanjay R; Forgione, Lisa A; Kosakovsky Pond, Sergei L; Smith, Davey M; Torian, Lucia V
Abstract : Investigating the molecular epidemiology of the HIV-1 epidemic in New York City demonstrates how past growth of HIV-1 transmission clusters is a reliable predictor of future cluster growth. These cluster growth dynamics are potentially useful for guiding public health action. Abstract: Background: HIV-1 genetic sequences can be used to infer viral transmission history and dynamics. Throughout the United States, HIV-1 sequences from drug resistance testing are reported to local public health departments. Methods: We investigated whether inferred HIV transmission network dynamics can identify individuals and clusters of individuals most likely to give rise to future HIV cases in a surveillance setting. We used HIV-TRACE, a genetic distance-based clustering tool, to infer molecular transmission clusters from HIV-1 pro/RT sequences from 65736 people in the New York City surveillance registry. Logistic and LASSO regression analyses were used to identify correlates of clustering and cluster growth, respectively. We performed retrospective transmission network analyses to evaluate individual- and cluster-level prioritization schemes for identifying parts of the network most likely to give rise to new cases in the subsequent year. Results: Individual-level prioritization schemes predicted network growth better than random targeting. Across the 3600 inferred molecular transmission clusters, previous growth dynamics were superior predictors of future transmission cluster growth compared to individual-level prediction schemes. Cluster-level prioritization schemes considering previous cluster growth relative to cluster size further improved network growth predictions. Conclusions: Prevention efforts based on HIV molecular epidemiology may improve public health outcomes in a US surveillance setting.